The Psychometric Properties of the Malay Version of Psychosocial Effects of Abnormal Pap Smear Questionnaire (PEAPS-Q): A Confirmatory Factor Analysis - Aniza, Abd Aziz; Mardiana, Mansor; Afiqah, Mat Zin (2018)
Introduction: The PEAPS-Q was used to assess the psychosocial effect of women with abnormal Pap smear results. The aim of this study was to measure the validity and reliability of PEAPS-Q in Malay language. Methods: A total of 218 respondents had participated in this cross-sectional study. Confirmatory construct validity and internal consistency assessments were analysed using SPSS Amos version 21.0 after the process of translation, content validity, face validity and exploratory factor analysis. Results: The first model directly confirmed the original four constructs. It demonstrated an acceptable factor loading (0.47- 0.96), domain to domain correlation (0.19-0.78) and best fit [Chi-squared/degree of freedom = 2.200, Goodness of Fit Index (GFI) = 0.901, Tucker-Lewis Index (TLI) = 0.936, Comparative Fit Index (CFI) = 0.950, Root Mean square Residual (RMR) = 0.073 and Root Mean Square Error of Approximation (RMSEA) = 0.074]. The Cronbach's α and composite reliability of the domains were excellent which ranged from 0.75 to 0.85 and 0.76 to 0.85, respectively. Conclusion: The Malay version PEAPS-Q was a valid and reliable instrument to be applied among women in Malaysia setting.